2022
DOI: 10.1039/d2sc01388f
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the mode of action and supramolecular assembly of teixobactin analogues in Bacillus subtilis

Abstract: Teixobactin has been the source of intensive study and interest as a promising antibiotic, because of its excellent activity against drug-resistant Gram-positive pathogens and its novel but not yet fully...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Of cells, 500 μl were centrifuged at 3,000 g for 5 min. The supernatant was discarded, and the cells were resuspended in 200 μl solution from a 1 μg ml −1 stock of the fluorescent analogue 26 Lys(Bodipy FL) 10 -teixobactin. The cells were allowed to incubate for the desired timepoints (1 min, 15 min and 45 min) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of cells, 500 μl were centrifuged at 3,000 g for 5 min. The supernatant was discarded, and the cells were resuspended in 200 μl solution from a 1 μg ml −1 stock of the fluorescent analogue 26 Lys(Bodipy FL) 10 -teixobactin. The cells were allowed to incubate for the desired timepoints (1 min, 15 min and 45 min) at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…f , Static 31 P ssNMR spectra show membrane perturbation induced by teixobactin (cyan line) in contrast to the untreated lipid II-doped DOPC large unilamellar vesicles (black dashed line). g , Confocal microscopy with B. megaterium incubated in the presence of a fluorescent teixobactin analogue 26 . Intense, elongated teixobactin clusters form fast and get more compact after 45 min.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…155 Recent studies have suggested that the bactericidal nature of teixobactin comes not only just from the sequestration of lipid II and thus from inhibiting the biosynthesis of peptidoglycan, but also from the resulting teixobactin fibril that displaces phospholipids, compromising the membrane integrity. 153,156,157 Since the discovery of teixobactin, the structurally similar hypeptin and clovibactin have also been characterized (Fig. 11).…”
Section: Teixobactinmentioning
confidence: 99%
“…This has resulted in the synthesis of various teixobactin analogues with enhanced and distinct modes of action, such as supramolecular assembly, which ultimately disrupts the cell membrane. [ 14 ].…”
Section: Revisiting Natural Products As a Source Of Novel Antibioticsmentioning
confidence: 99%